Performance of 'Oneco' mandarin on six rootstocks in South Brazil - Mateus Pereira Gonzatto; Alisson Pacheco Kovaleski; Eduardo Cesar Brugnara; Roberto Luis Weiler; Ivar Antônio Sartori; Jurandir Gonçalves de Lima; Renar João Bender; Sergio Francisco Schwarz (Pesquisa Agropecuária Brasileira, 2011)
The objective of this work was to assess the effect of six rootstocks on yield, fruit quality, and growth of 'Oneco' mandarin during the first seven harvesting seasons, in Butiá, Rio Grande do Sul State, Brazil. The rootstocks evaluated were: 'Swingle' citrumelo (Citrus paradisi × Poncirus trifoliata), 'Caipira' orange (C. sinensis), 'Troyer' citrange (C. sinensis × P. trifoliata), 'Rangpur' lime (C. limonia), 'Volkamer' lemon (C. volkameriana), and 'Flying Dragon' trifoliata orange (P. trifoliata var. monstrosa). Plants budded onto 'Flying Dragon' had the lowest vegetative development, which indicates the dwarfing characteristics of this rootstock, and had the highest mean production efficiency, despite low yield. Plants grafted on 'Volkamer' lemon and 'Rangpur' lime had the highest alternate bearing. Under the experimental conditions evaluated, the most adequate rootstocks for mandarin 'Oneco' are 'Swingle' citrumelo and 'Troyer' citrange, regarding fruit yield and quality.